Moral Development Strategies To Shape Elementary School Students' Anti-Bullying Attitudes - Yatiman, Yatiman; Khozin, Khozin; Hakim, Rahmad (IJGIE (International Journal of Graduate of Islamic Education), 2025)
This study explores the moral development strategies implemented at SD Muhammadiyah Suro to foster anti-bullying attitudes among elementary students. Bullying remains a serious concern in school environments, with detrimental impacts on children's physical, psychological, and social well-being. To mitigate this issue, schools are required to adopt comprehensive moral education approaches that nurture empathy, respect, and prosocial behavior. This research employed a qualitative approach using a case study method. Primary data were obtained through in-depth interviews with the school principal, teachers, and selected students, as well as classroom observations. Secondary data were collected through document analysis of school policies and programs related to moral development. The findings reveal that the school integrates several key strategies: Islamic-based character education, positive behavior habituation, teacher modeling, and restorative conflict resolution practices. These efforts are also supported by extracurricular activities that promote empathy and collaboration among students. The study concludes that moral development strategies grounded in religious and character values, when consistently applied and supported by the involvement of educators, parents, and the broader school community, can cultivate a safe, respectful, and inclusive school environment. Such strategies play a crucial role in shaping students’ moral awareness, fostering resilience, and promoting social responsibility.